Association of single nucleotide variants of the clock gene (rs1801260) with seizures after alcohol withdrawal - R. S. Achuvakov; I. S. Efremov; D. V. Bobrik; U. S. Efremova; R. A. Khakimova; A. R. Asadullin (Медицинский вестник Юга России, 2024)
Objective: to study the association of single nucleotide variants of the CLOCK gene (rs1801260) and seizures aﬅer alcohol withdrawal.Materials and methods: 399 patients were analyzed, including 83 women (21%) and 316 men (79%). The average age of the patients was 41.52±8.42 years. The patients were divided into 2 groups. The main group (patients who suﬀered a seizure in a hospital setting) consisted of 108 patients, 12 women (11%), 96 men (89%), and the comparison group consisted of 291 patients, 71 (25%) women and 220 (75%) men. The examination of patients took place from February 2019 to August 2023. The laboratory study included a comparative genetic examination of two groups of patients: the ﬁrst group — patients with alcohol dependence syndrome with seizures aﬅer alcohol withdrawal (F10.2); the second group — patients with alcohol dependence syndrome (F10.2) without seizures aﬅer alcohol withdrawal. Statistical processing was carried out using Microsoﬅ Excel, IBM SPSS Statistics 26. During the frequency analysis, the criterion χ² (Pearson Chi-squared) was used, and the odds ratio for each of the genotypes was estimated. The diﬀerences were recognized as statistically signiﬁcant at a signiﬁcance level of p<0.05. ><0.05.Results: when conducting a frequency analysis of the occurrence of seizures aﬅer alcohol withdrawal, carriers of the CC genotype had seizures much less frequently than carriers of other genotypes.Conclusion: the presence of the T allele of the CLOCK gene in the genotype is associated with seizures aﬅer alcohol withdrawal. Moreover, carriers of the homozygous genotype have a higher chance of experiencing seizures than carriers of the homozygous genotype.